Physical and photoluminescence investigations of Eu3+ doped gadolinium borate scintillating glass. (November 2022) - Damdee, B.; Kirdsiri, K.; Kim, H.J.; Yamanoi, K.; Wongdamnern, N.; Kidkhunthod, P.; Rajaramakrishna, R.; Kaewkhao, J.
Abstract: The bright reddish-orange emitting Eu 3+ -doped gadolinium borate glasses of 25Gd2 O3 -(75-x) B2 O3 -xEu2 O3 (GdBEu) (x = 0.1, 0.3, 0.5, 1.0, 3.0, 5.0, 7.0, and 9.0 mol%) were fabricated by melt-quenching technique at 1400 °C for 3 h. All GdBEu glasses were investigated the photoluminescence, scintillation, and lasing potential properties. The energy transfer processes from Gd 3+ →Eu 3+ in these glasses were discovered. Photons in the ultraviolet, visible, and near-infrared region wavelengths were absorbed by glasses. The photoluminescence excitations were performed at 275 nm and 394 nm, respectively. When the energy transferred from Gd 3+ to Eu 3+, luminescence features revealed an intense red emission with a wavelength of 614 nm ( 5 D0 → 7 F2 ). The glass's optimum Eu 3+ ion concentration was 7.0 mol%, corresponding to the maximum emission intensity. Judd-Ofelt parameters were calculated from the emission spectra and the radiative properties of several excited states were examined, including the transition probability (AR ), branching ratio (βR ), stimulated emission cross-section (σe ), and decay time (τR ). Once the Eu 3+ concentration increased from 0.1 to 9.0 mol%, the decay time of the 5 D0 level dropped from 1.824 ms to 1.585 ms. The colors of glasses were confirmed by the Commission internationale de l'éclairage (CIE) chromaticity diagram. The glass samples had a peak area of radioluminescence (RL) spectrum 18% of BGO scintilltation crystal. Highlights: Gadolinium borate glasses doped with Eu 3+ were synthesized. The emission transitions from 5 D0 .→ 7 F1, 2, 3, 4 observed. Emission intensities increased up to 7% of the Eu2 O3 . Maximum integral scintillation efficiency was 18% compared BGO.